PUBLIC RELATIONS IN TURKEY FROM WOMEN'S PERSPECTIVE - GÜVEN, DENİZ; ÇERÇİ, MERVE (ISTANBUL KULTUR UNIV, 2018)
When foreign capital entered the country and new government policies were developed in this area in the end of 1960s, studies on public relations increased in Turkey. In the historical process to the present, many women have had an active part in development of the discipline. People who entered the profession between 1960s and 1990s realised the importance of public relations in its early period, and these people conducted miscellaneous studies. People who preferred this profession in 1990s and worked in the sector, were affected from socio-economic factors and education policies, and the discipline acquired a new dimension. With developments in mass media in 2000s and communication technologies' becoming important parts of our lives, the discipline entered into a new process of evolution. This study aims to analyse the topic by centering woman perspective of the development of the discipline. Since the representatives both from the old and young generation are brought together within the context of the study, it differs from other studies and brings new stratas to the topic. In this study in which in-depth interview method was used, it is determined that women make an effect of catalyst in the development of public relations and that they formed an important basis for the development of the process.
Keywords: History of Public Relations in Turkey; Public Relations; Perspective of Woman; RELATIONS HISTORY